Influence of granule properties and concentration on cork-cement compatibility - Karade, Sukhdeo R; Irle, Mark; Maher, Kevin (Holz als Roh- und Werkstoff, 2006)
Cork granules are produced as by-products and waste by the cork processing industries that make ‘bottle stoppers’ as a main product. These granules are of low density and could be used as lightweight aggregates for making concrete. This paper describes an investigation carried out to assess the compatibility of cork granules with cement for the manufacture of lightweight cementitious composites. Five different grades of cork granules varying in terms of size and density were investigated. The effects of extractives, particle size and density of the cork granules were studied. The results indicate that these parameters affect cement hydration in a complex way. At lower concentrations of cork (10%), only the extractives have an inﬂuence on hydration behaviour. At higher cork concentrations (20% and 30%), however, particle size and density also affect the compatibility. Nevertheless, cork granules are found to be compatible with cement.
Keywords: cement; composites; Cork granules; Density; hydration (voyant)